Oxidative Stress in Children with Sexual Abuse May Be Elevated and Correlate with History of Psychiatric Treatment: A Cross-Sectional Case-Control Study - (:unkn) unknown (YERKURE TANITIM & YAYINCILIK HIZMETLERI A S, 2019)
Objective: There is an increased oxidative stress process in psychiatric disorders that may result due to chronic stress exposure. Lipid peroxidation and chronic inflammation also increase oxidative stress according to the model of inflammation observed in psychiatric diseases. Oxidative stress can also damage the central nervous system by glutamate-mediated excitotoxicity and hyperstimulation of N-methyl-D-aspartate (NMDA) receptors. Direct studies examining the relationship between sexual abuse and oxidative stress are limited in the literature. In this study, we aimed to examine the oxidative stress parameters, psychopathologies and related sociodemographic factors in adolescents who were exposed to sexual abuse. Methods: Patients aged between 10-17 years old who had been sexually abused and had a history of at least one year of sexual abuse were compared with age and gender matching control cases. Our sample consisted of 50 cases that had sexual abuse (42 female and 8 male) and 40 controls (32 female and 8 male). The socio-demographic information of the participants was obtained with a detailed form which was constituted by the researchers. Assessment of psychopathology and clinical functioning was carried out with the Turkish version of the Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime Version (K-SADS-PL). Adolescents were also examined with Beck Depression Inventory, Beck Anxiety Scale, Post Traumatic Response Scale, Ways of Coping Inventory, Strengths and Difficulties Scale and List of Negative Life Events. Results: The mean age of the cases was 14.88 +/- 2.16 years in the abuse group and 14.90 +/- 2.18 years in the control group. School continuity in the sexual abuse group was significantly lower. Moreover, sexual abuse cases were coming from distressed families with relatively much lower monthly income. Penetration was 60%, and physical violence was 46% reported during abuse. Suicide attempt was described in 34% of the abuse group. Before the abuse, psychiatric referrals were present in 46% of the cases. The most common diagnoses after abuse were as follows; 78.2% Post Traumatic Stress Disorder (PTSD), 78.2% depression, and 60.8% specific phobia. WISC-R scores in the abuse group were lower compared to the control group. Functionality scores were lower than controls whereas the Beck Depression Inventory, Beck Anxiety Scale, Post Traumatic Response Scale and scores of Negative Life Events Scales were higher in the study group. Conclusions: Level of oxidative stress assessed by total oxidant status (TOS), total antioxidant status (TAS) and oxidative stress index (OSI) showed a significantly higher oxidative stress and diminished antioxidant process profile in the sexual abuse group. TOS and OSI values were significantly higher while TAS values were significantly lower compared to the controls. Since oxidative stress mechanism accelerates the cell cycle, it leads to premature cell death which may result in many neuropsychiatric illnesses that have been described in this study of abused adolescents. A more detailed study of oxidative stress mechanisms in adolescents in terms of an increase in the risk of physical disease, as well as possible adverse effects on life span and deterioration in the quality of life and increased risk of acquiring a chronic illness, would be meaningful in seeking answers to epigenetic questions.
Keywords: Adolescent; oxidative stress; psychopathology; sexual abuse; total oxidant status; total antioxidant status